Assessment of relationship among traits and genotypes for melon (Cucumis melo) breeding - RAHMATUN NISFUL MAGHFIROH; WILLY BAYUARDI SUWARNO; SOBIR SOBIR; ENDANG GUNAWAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Maghfiroh RN, Suwarno WB, Sobir, Gunawan E. 2023. Assessment of relationship among traits and genotypes for melon (Cucumis melo) breeding. Biodiversitas 24: 4523-4531. Melon (Cucumis melo L.) is widely consumed as fresh fruit or juice, and therefore deeper analyses of fruit quality are needed for future breeding purposes. Breeders have a role in providing improved melon varieties that suit consumer ideotypes or preferences. This study aimed to (i) evaluate the performance of melon genotypes, (ii) estimate the correlation between quantitative traits, and (iii) determine the clustering among genotypes based on plant and fruit traits. This research evaluated 24 genotypes from inodorus, reticulatus, and makuwa groups that were carried out from March to June 2022 at a greenhouse in the Tajur experimental station of the Center for Tropical Horticulture Studies, Bogor, Indonesia. IPB HD 2-111 and IPB HD 2-100 had good quality based on soluble solids content, fruit shape, flesh texture, and rind color, and G30 was relatively superior on flesh thickness, fruit weight, and vitamin C. Based on the multiple regression analysis, it was known that petal width, petiole length, and days to harvest were significantly affected the proportion of fruit cavity width to the fruit diameter. The adjusted coefficient of determination (R2) was 0.569. Cluster analysis grouped 23 genotypes into three main clusters based on the neighbor-joining method. These results may be useful for selection in melon breeding programs.